Acute Renal Failure Due to Jengkol Intoxication in Children - Husein Alatas (Indonesian Pediatric Society, 1994)
JengkoL intoxication is well-known in Indonesia. We report a series of 39 parents with jengkol intoxication admitted to the Department of Child Health Cipto Mangunkusumo Hospital, Jakarta, during the period of 1984 through 1993. Patients ranged in age from 3 to 14 years. The male to female ratio of all cases was 1.8 to 1 but the ratio of patients suffering from acute renal failure was 5.7 to 1. Oliguria or anuria presented in all cases with acute renal failure. Three patients underwent peritoneal dialysis which gave rapid improvement; 2 patients had died due to acute renal failure before dialysis could be performed. When compared with previous reports, it seems that the admission for jengkol intoxication has been declining. Change in the way of consuming the bean and increasing number of hospitals in Jakarta may be responsible for the decline of cases admitted.